2020
DOI: 10.1016/j.celrep.2019.12.086
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Signaling Stimulates Autophagy to Regulate Stem Cell Maintenance and Lipid Homeostasis in the Drosophila Testis

Abstract: SUMMARY Although typically upregulated upon cellular stress, autophagy can also be utilized under homeostatic conditions as a quality control mechanism or in response to developmental cues. Here, we report that autophagy is required for the maintenance of somatic cyst stem cells (CySCs) in the Drosophila testis. Disruption of autophagy in CySCs and early cyst cells (CCs) by the depletion of autophagy-related (Atg) genes reduced early CC numbers and affected CC function, resemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 92 publications
7
53
0
Order By: Relevance
“…Against this background, researchers have recently proposed various schemes to induce ferroptosis (52). The efficacy of ferroptosis induction therapy in treating EGFR mutant LUAD and EGFR-TKI-resistant LUAD has not been reported but it has been proven that the activation of the EGFR pathway can increase the expression of the proteins in the lipid peroxide reduction system (25)(26)(27)(28)(29) while also promote the accumulation of intrinsic lipid peroxides (53)(54)(55). For example, the activation of the EGFR-p62-Keap1-NRF2 pathway in tumor cells can induce xCT protein expression and contribute to ferroptosis resistance (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Against this background, researchers have recently proposed various schemes to induce ferroptosis (52). The efficacy of ferroptosis induction therapy in treating EGFR mutant LUAD and EGFR-TKI-resistant LUAD has not been reported but it has been proven that the activation of the EGFR pathway can increase the expression of the proteins in the lipid peroxide reduction system (25)(26)(27)(28)(29) while also promote the accumulation of intrinsic lipid peroxides (53)(54)(55). For example, the activation of the EGFR-p62-Keap1-NRF2 pathway in tumor cells can induce xCT protein expression and contribute to ferroptosis resistance (27).…”
Section: Discussionmentioning
confidence: 99%
“…Bersuker et al (24) displayed that ferroptosis inhibitor protein 1 (FSP1), also known as apoptosis-inducing factor mitochondrial associated protein 2 (AIFM2), may inhibit cell ferroptosis through GPX4independent pathways. Interestingly, a growing body of evidence has shown that EGFR signaling pathway participates in ferroptosis regulation (25)(26)(27)(28)(29). However, it is still unclear whether ferroptosis induction can be used as a new strategy to treat EGFR mutant LUAD or overcome the acquired and intrinsic EGFR-TKI resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that increasing ATG9B predicted poor prognosis. EGFR is well studied in melanoma and has been found to activate autophagy and melanoma cell mobility 38,39 . Another interesting finding is that HER3, a member of the EGFR family, is able to reactivate RAS-ERK signaling, allowing tumor cells to escape from the inhibitory effects of BRAF inhibitors 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that autophagy participates in the regulation of inflammation to prevent the development of autoimmune and inflammatory diseases (18). Autophagy not only eliminates macromolecules in autophagic cells, but also clears damaged organelles to maintain intracellular homeostasis (19). Microglia are an important type of neuroimmune cell, which in their activated state, induce tissue repair and neuroprotection by releasing neurotrophic factors and phagocytizing damaged nerve cells (20).…”
Section: Bone Marrow Stromal Cells-derived Exosomes Target Dab2ip To mentioning
confidence: 99%